Natural resource rents, autocracy and economic freedom - Morten Endrikat (Philipps-University Marburg, School of Business and Economics, 2021)
This paper theoretically and empirically investigates the effect of natural resource rents on the process of economic liberalization and a potential moderating effect of the level of democracy. A simple political-economic model is developed in which the government in an autocratic country faces a trade-off between liberalizing the economy to broaden the tax base on the one hand and consolidating its political power by preventing the rise of an economically independent middle class striving for political participation on the other hand. Whilst the theoretical model predicts that rents from natural resources lead to economic liberalization in both autocratic and democratic countries, the empirical analysis finds evidence that increasing resource abundance may lead to deliberalization in autocracies but may promote liberalization in democracies. The empirical evidence is robust to using both static panel data methods that control for unobserved country heterogeneity as well as a dynamic GMM estimator that further controls for potential endogeneity issues.
Keywords: D73; H20; O13; O39; Q32; Q38; 330; Natural Resources; Resource Curse; Institutions; Taxation; Economic Liberalization; Entrepreneurship